Isolation of potential biosurfactant producer from soil contaminated with palm oil mill effluent - Farah Fatin Fasehah Ahmad Fazil (2016)
Biosurfactants are amphiphilic compounds produced by various bacteria and fungi which reduce surface and interfacial tension. The unique properties of biosurfactants make them possible to replace or to be added to synthetic surfactants which are mainly used in food, cosmetics and pharmaceutical industries and in environmental applications. The main objective of this study is to isolate and characterize potential biosurfactant producer from soil contaminated with palm oil mill effluent. Soil samples were collected from overﬂow mixing pool drain (M1) and anaerobic mixing pool drain (A1) of a palm oil mill. Six potential biosurfactant producers were successfully isolated. The isolation was carried out in Mineral Salt Medium (MSM) supplemented with 1% crude palm oil as sole carbon source for bacterial growth. Production of biosurfactant were screened by emulsiﬁcation assay, drop collapse assay and oil spreading assay. M1-2 showed higher potential of biosurfactant as it showed highest emulsification index which is 57.88% and also scored positive results for other two test. A1-2 showed lowest emulsification index which was 35%. The higher emulsification index might indicates higher activity of biosurfactant.